24th International Conference on Offshore Mechanics and Arctic Engineering: Volume 3 2005
DOI: 10.1115/omae2005-67354
|View full text |Cite
|
Sign up to set email alerts
|

FEA of Out-of-Plane Fatigue Mechanism of Chain Links

Abstract: Several mooring chains of an off-loading buoy failed after only 8 months of service. These chains were designed according to conventional fatigue assessment using API RP 2SK T-N curves to a fatigue life of 20 years with a factor of safety equal to 3 on life. Of particular interest is that the mooring chain failure underwent significant mooring chain motions that caused interlink rotations. Although traditionally neglected, these interlink rotations, when combined with significant chain tensions can cause bendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…OPB stress vs interlink angle curves presented in the present paper are confirmed by FEA, see Ref [1]. Sufficient data must be gathered to improve our understanding of stresses in chains under high pretensions.…”
Section: Conclusion and On Going Worksupporting
confidence: 70%
See 1 more Smart Citation
“…OPB stress vs interlink angle curves presented in the present paper are confirmed by FEA, see Ref [1]. Sufficient data must be gathered to improve our understanding of stresses in chains under high pretensions.…”
Section: Conclusion and On Going Worksupporting
confidence: 70%
“…[1]) of two links has shown that, under a tension equal to proof load, the surface of contact between the two links is permanently deformed, see Figure 6. Plastic elastic FEA (see Ref.…”
Section: Locking Modementioning
confidence: 99%
“…For Scenarios 2 and 3, the most critical location of mooring chain links prone to fatigue damage moves to the middle of crown section (D-D cross-section) as shown in Figure 8 [6][7][8]. Figure 9 shows a typical normal stress distribution over the cross-section described in Figure 8.…”
Section: Finite Element (Fe) Analysismentioning
confidence: 99%
“…Melis et al [6] presented experimental results of mooring chain stresses induced by OPB. Vargas and Jean [7] compared mooring chain stresses calculated by FE method with experimental results of Melis et al [6]. Lassen et al [8] and Lassen et al [9] performed a mooring chain fatigue life using an S-N curves based approach, and the behaviour of chain links subjected to tension and OPB was investigated by both experimental and FE methods.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fatigue damage of ring chain, Li 4 summarized the fatigue damage mechanism of ring chain in coal mine and its influencing factors. Melis et al 5 and Vargas and Jean 6 analyzed the fatigue damage mechanism of marine mooring anchor chain. Dong et al 7 proposed the empirical prediction method of fatigue life of ring chain of scraper conveyor.…”
Section: Introductionmentioning
confidence: 99%